2016
DOI: 10.31219/osf.io/u6m2m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The religiosity as social value hypothesis: A replication and extension

Abstract: Are religious people psychologically better or worse adjusted than their non-religious counterparts? Hundreds of studies have reported a positive relation between religiosity and psychological adjustment. Recently, however, a comparatively small number of cross-cultural studies has questioned this staple of religiosity research. The latter studies find that religious adjustment benefits are restricted to religious cultures. Gebauer, Sedikides, and Neberich (2012b) suggested the religiosity-as-social-value hypo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…To obtain a benchmark for the size of the effects of P-C personality fit, we also examined the extent to which the fit between person and city religiosity predicted selfesteem. As found previously (Gebauer, Sedikides, Schönbrodt, et al, 2015), there was a significant interactive effect of individual-level and city-level religiosity on selfesteem. The effect size was similar to the sizes of the effects observed for personality traits.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To obtain a benchmark for the size of the effects of P-C personality fit, we also examined the extent to which the fit between person and city religiosity predicted selfesteem. As found previously (Gebauer, Sedikides, Schönbrodt, et al, 2015), there was a significant interactive effect of individual-level and city-level religiosity on selfesteem. The effect size was similar to the sizes of the effects observed for personality traits.…”
Section: Discussionsupporting
confidence: 85%
“…No previous research has examined the impact of P-C personality fit on self-esteem, so to establish an effectsize benchmark for contextualizing our results, we also examined the impact of P-C religiosity fit on self-esteem. That is, we ran the same fit analyses using a variable that is distinct from personality, but that is also linked to selfesteem (Gebauer, Sedikides, Schönbrodt, et al, 2015) and that has been shown to vary geographically (Motyl, Iyer, Oishi, Trawalter, & Nosek, 2014).…”
mentioning
confidence: 99%
“…To the extent that these factors diminished the validity of the personality estimates, the effects reported here are likely to be diminished too, so any effects should be interpreted as conservative estimates. However, indirect evidence for the validity of the personality estimates is provided by previous research undertaken at regional levels, which has shown convergence between analyses based on self-reports and informant reports (e.g., Gebauer et al, 2014) and has demonstrated reasonably strong levels of state-level stability Elleman, Condon, Russin, & Revelle, 2017;Rentfrow et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We also note, however, that more research is needed to further explore the source of country‐to‐country variation among these effects. One possibility, for example, is to align countries in relation to spatial proximity, in which countries more geographically close to each other are more similar (e.g., Gebauer et al, ), or proximity in relation to other dimensions more relevant to the focus of research such as school policies in relation to tracking. Indeed, as shown by previous research, the most critical variable is the nature of tracking in the school system—operationalized here as variation in school‐average achievement (e.g., Marsh & Seaton, ).…”
Section: Discussionmentioning
confidence: 99%